Cardioneuroablation for treating refractory vasovagal syncope - Dando, L; Yoo, J; Howick, JF; Van Niekerk, CJ; McLeod, CJ (SA Heart Journal, 2025)
Vasovagal syncope (VVS), also known as neurocardiogenic syncope, often presents significant management challenges in patients with frequent refractory episodes. Cardioneuroablation (CNA) targets ganglionated plexi (GP) through catheter ablation to mitigate excessive vagal tone. This case report demonstrates the successful application of CNA in a patient with recurrent neurocardiogenic syncope, initially characterised by a mixed response with a minimal cardioinhibitory component and subsequent electrophysiological evaluation, which revealed significant cardioinhibitory and vasodepressor components, prompting a targeted ablation approach. While future studies are required to evaluate the longterm safety and efficacy, this case adds to the growing evidence that supports CNA as a safe and effective intervention for select patients with refractory VVS. Keywords: cardioneuroablation, vasovagal syncope, cardioinhibitory response, mixed response, vasodepressor response